Institutional Ownership and Integrated Reporting in the Digital Age: A Conceptual Exploration of Firm Performance in Malaysia - Mohd Ali, Salsiah; Md Zaini, Syeliya; Mohd Ali, Mazurina; Hambali, Siti Syaqilah Binti (Information Management and Business Review, 2023)
This concept paper explores the potential moderating role of institutional ownership on the relationship between Integrated Reporting (IR) adoption and firm performance within the context of the digital business era, specifically in Malaysia. Drawing on stakeholder theory and agency theory, the paper highlights the dual role institutional investors can play in shaping a firm’s adoption of IR and its subsequent effect on performance. Through a comprehensive review of the existing literature, the paper unravels the unique challenges and opportunities that arise when adopting IR in the digital business landscape, particularly in developing nations with concentrated ownership structures. The study emphasizes the importance of nuanced understanding to promote corporate transparency and sustainable value creation. It aims to guide future research endeavors, informing policymaking and business practices to optimize the benefits of IR in the digital era. The conceptual framework and discussions put forth in this paper are intended to contribute to the broader academic discourse on the evolution of IR practices in the digital business era.